An electrochemical aptasensor for ATP based on a configuration-switchable tetrahedral DNA nanostructure. Issue 25 (17th June 2020) - Jing, Cheng; Chen, Haohan; Cai, Rongfeng; Tian, Yaping; Zhou, Nandi
Abstract : A novel electrochemical aptasensor for ATP was developed based on an aptamer-embedded configuration-switchable tetrahedral DNA nanostructure (TDN) and the formation of a G-quadruplex. Abstract : A novel electrochemical aptasensor for ATP was developed based on an aptamer-embedded configuration-switchable tetrahedral DNA nanostructure (TDN) and the formation of a G-quadruplex. This unique TDN was formed through the self-assembly of four specially designed single-stranded DNA (ssDNA) sequences (S1, S2, S3 and S4). The TDN was immobilized on the surface of a Au electrode through the thiol groups at the 5′-end of S1, S2 and S3. Five edges of the TDN were designed to form a double helix to preserve the structural robustness of the tetrahedron, while the ATP aptamer embedded sequence (S3) was designed to be located at the rest edge. The two terminals of S4 at the same edge were composed of two split G-quadruplex-forming sequences, which were non-complementary to the aptamer. This edge offered the configuration-switchable characteristic of the TDN. In the absence of ATP, the TDN remained in a relaxed state, and the G-quadruplex cannot form due to the large distance between the split G-quadruplex-forming sequences. However, in the presence of ATP, the aptamer combined with ATP and shortened the distance between the split sequences, resulting in the taut state of the TDN and the formation of a G-quadruplex at the edge. After the addition of hemin, the differential pulse voltammograms (DPVs) were used to quantify ATP. The sensor revealed a dynamic response range from 0.1 nM to 1 μM, with a detection limit of 50 pM. In addition, the specificity and practicability in real samples were also verified, indicating its potential applications.